Desain Simulasi Cisco Pada Studi Kasus Optical Transport Network (OTN) - Fina Ayu Lestari; Deny Exka Saputra; Yudi Syah Pratama; Didik Aribowo (CV. Alim's Publishing, 2023)
Network traffic has increased exponentially, revenue has not maintained the same pace. New methods should be explored to reduce this gap between traffic and revenue. While the OTN protocol implemented via DWDM offers many management and control area benefits, overall network CAPEX can be minimized in the design phase by planning both layers simultaneously. Multilayer redirection finds a middle ground between opaque and transparent networks across all traffic volumes. Cisco is the main equipment that is commonly used in Wide Area Networks or Wide Area Networks (WAN). With a Cisco router, information can also be forwarded to the address to be addressed. In this study, discusses the Optical Transport Network (OTN) and how the network topology forms in Cisco Packet Tracer 6.2 software.